Design and synthesis of novel porphyrinated polyimide nanofibers as dissolved oxygen sensor: The role of electro-activity and orientation. (February 2019) - Lei, Huanyu; Lu, Jiaming; Dong, Guoqing; Tian, Guofeng; Qi, Shengli; Wu, Dezhen
Abstract: Two novel porphyrinated polyimides, 3, 3′, 4, 4′-biphenyltetracarboxylic dianhydride (BPDA)/4, 4′-Oxydianiline (ODA)/iron 5, 10-bis(4-aminophenyl)-15, 20-diphenylporphyrin (FeDATPP) and 4, 4′-hexafluoroisopropylidene diphthalic anhydride (6FDA)/ODA/FeDATPP, abbreviated as BOFe and 6OFe, were synthesized and electrospun into nanofibers for dissolved oxygen (DO) sensing. The effects of electro-activity (i.e., electron-withdrawing ability of BPDA, 6FDA and FeDATPP when these units were binding with DO) and the roles of the nanofiber orientation in DO sensing were investigated. Electrochemical characterization indicates that the current values in Cyclic Voltammograms (CV) exhibits linear correlation with the DO concentration, with the correlation coefficient R2 varying from 0.9461 to 0.9958, suggesting the excellent DO sensing performance of the synthesized porphyrinated polyimides. Meanwhile, it is found that the oxygen reduction behaviors in DO sensing were vastly altered due to the different electro-activity and orientation structures of the porphyrinated polyimides nanofibers. An unusual side-on porphyrin-O2 configuration and charge transfer mechanism during DO sensing were clarified upon molecular simulation. The present work provides two novel porphyrinated polyimides for DO sensor applications. Graphical abstract: Highlights: Two novel porphyrinated polyimides were synthesized and electrospun into nanofiber membranes for dissolved oxygen (DO) sensing. Performance of DO sensing varies among membranes containing different electron-withdrawing units. Performance of DO sensing increases with the fiber orientation degree. An unusual side-on porphyrin-O2 configuration and charge transfer in DO sensing were clarified by molecular simulation.